Analysis of formulated detergents. Quantitative test methods. Method for determination of hydrolyzable and non-hydrolyzable anionic-active matter content after hydrolysis under alkaline conditions Part 3-3.2, (30th December 1983) - British Standards Institution,
No abstract available